PMMA or PVDF films blended with β-diketonate tetrakis EuIII or TbIII complexes used as downshifting coatings of near-UV LEDs - Beltrame, Ariane C. F. [UNESP]; Bispo-Jr, Airton G.; Canisares, Felipe S. M. [UNESP]; Fernandes, Ricardo V.; Laureto, Edson; Lima, Sergio A. M. [UNESP]; Pires, Ana M. [UNESP] (Royal Society of Chemistry (RSC), 2023)
Luminescent LnIII complexes incorporated in polymeric films exhibit narrow emission bands and absorption within the near-UV/blue spectral range, and enhanced phostability, which qualify them to be explored for solid-state lighting. Herein, (C26H56N)[Eu(dbm)4] and Na[Tb(acac)4], (C26H56N+ = didodecyldimethylammonium, dbm− =1,3-diphenyl-1,3-propanedionate, acac− = acetylacetonate), were dispersed in PMMA or PVDF films to protect them from degradation, and the obtained blends were applied as downshifting coatings on near-UV emitter LEDs. Upon such excitation, both EuIII and TbIII complexes emit red or green light with absolute emission quantum yields of 6.4 and 99%, respectively. The complex amount within films influences the photophysical parameters due to multiphotonic deactivation, and formation of agglomerates. For the PMMA-based LED prototypes, the LnIII emission is well-observed while for the PVDF ones, only a poor LnIII emission is detected due to their opacity. Therefore, the PMMA-based systems are better candidates to be used as luminescent coatings of near-UV LEDs for solid-state lighting.